2018
DOI: 10.1039/c8dt03283a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into HCO2H dehydrogenation and CO2 hydrogenation catalyzed by Ir(Cp*) containing tetrahydroxy bipyrimidine ligand: the role of sodium and proton shuttle

Abstract: Catalytic HCO2H dehydrogenation by Ir(Cp*) tetrahydroxy bipyrimidine is influenced not only by the protonation states but also by the involvement of Na+ and the availability of HCO2H as a proton shuttle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…28 Recently, Fink and Laurenczy have also suggested that H 3 O + could be the proton source for liberating H 2 gas in their recent report on FAD catalyzed by a Rh complex. 54 Computational studies by Surawatanawong et al 55 and Liu et al 56 also demonstrate that hydronium ion is the proton source for protonation of metal-hydride bond to produce molecular hydrogen in their case as well. Thus, the possibility of protonation by hydronium ion was also considered for investigation in this work.…”
Section: Resultsmentioning
confidence: 96%
“…28 Recently, Fink and Laurenczy have also suggested that H 3 O + could be the proton source for liberating H 2 gas in their recent report on FAD catalyzed by a Rh complex. 54 Computational studies by Surawatanawong et al 55 and Liu et al 56 also demonstrate that hydronium ion is the proton source for protonation of metal-hydride bond to produce molecular hydrogen in their case as well. Thus, the possibility of protonation by hydronium ion was also considered for investigation in this work.…”
Section: Resultsmentioning
confidence: 96%
“…The second reaction path is where a hydronium ion (hydrated proton from the water solvent) acts as the proton source (pathway ii). Liu et al and Wonglakhon and Surawatanawong have identified this pathway as one of the possible protonation routes for H 2 generation. , Additionally, as the chosen catalyst contains a N–H moiety on the imidazoline ring, a FA dimer stabilized by the intermolecular hydrogen bonding between the two FA molecules and γ-N–H functionality could be envisioned as the source of the proton for H 2 evolution (see pathway iii in Scheme ). There are also other possibilities where the N–H proton can participate in the mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to the critical hydride delivery step in the acid-assisted ester hydrogenation, 17 due to the highly electrophilic nature of CO 2 , 51 no assistance is required. 52 An extremely low barrier was calculated for direct hydride transfer associated with TS6 (Δ G ‡ = 11.7 kcal mol −1 relative to 1 ). No interaction of the formally anionic O-center of the emerging formate with the Rh III center was observed in the IRC corresponding to TS6 (see the ESI† for animation), and immediately after hydride transfer, formate was found to dissociate from the coordination sphere leading to the formation of 5 .…”
Section: Reduction Of Co2via Direct Hydride Transfer From Rhiii–hmentioning
confidence: 99%